MVA vector expression of SARS-CoV-2 spike protein and protection of adult Syrian hamsters against SARS-CoV-2 challenge - Clement A. Meseda (Nature Portfolio, 2021)
Abstract Numerous vaccine candidates against SARS-CoV-2, the causative agent of the COVID-19 pandemic, are under development. The majority of vaccine candidates to date are designed to induce immune responses against the viral spike (S) protein, although different forms of S antigen have been incorporated. To evaluate the yield and immunogenicity of different forms of S, we constructed modified vaccinia virus Ankara (MVA) vectors expressing full-length S (MVA-S), the RBD, and soluble S ectodomain and tested their immunogenicity in dose-ranging studies in mice. All three MVA vectors induced spike-specific immunoglobulin G after one subcutaneous immunization and serum titers were boosted following a second immunization. The MVA-S and MVA-ssM elicited the strongest neutralizing antibody responses. In assessing protective efficacy, MVA-S-immunized adult Syrian hamsters were challenged with SARS-CoV-2 (USA/WA1/2020). MVA-S-vaccinated hamsters exhibited less severe manifestations of atypical pneumocyte hyperplasia, hemorrhage, vasculitis, and especially consolidation, compared to control animals. They also displayed significant reductions in gross pathology scores and weight loss, and a moderate reduction in virus shedding was observed post challenge in nasal washes. There was evidence of reduced viral replication by in situ hybridization, although the reduction in viral RNA levels in lungs and nasal turbinates did not reach significance. Taken together, the data indicate that immunization with two doses of an MVA vector expressing SARS-CoV-2 S provides protection against a stringent SARS-CoV-2 challenge of adult Syrian hamsters, reaffirm the utility of this animal model for evaluating candidate SARS-CoV-2 vaccines, and demonstrate the value of an MVA platform in facilitating vaccine development against SARS-CoV-2.